PRINSIP KEPEMIMPINAN ISLAM DALAM PANDANGAN AL-QUR'AN - Mubarok, Subhan (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2021)
Abstract The government, heads of state, or the leaders are always dealing with people consisting of various groups. The main task of the leader is to manage the group differences properly, If the leader couldn’t manage properly, it would be devastation. On the contrary, if the leader will be able to manage these differences well, it would create a harmonious life. Islam regulates all aspects of life based on the provisions of Allah SWT, including in the aspect of leadership. Therefore, this study aims to discuss the principles of Islamic leadership in the view of the Qur'an, and then the essence and meaning of leadership can be justified in more details. The results of this study indicates that the principles of Islamic leadership based on the Qur'an consist of three principles, there are; First, the human principle in the concept of the khalifah. Second, the principle of faith (iman) for leadership success. And third, the principle of ulil amri in governance.